Development of a Treatment Model for Pregnant Women Using Methamphetamine - Joomjana, Orapan (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Methamphetamine use among pregnant women is an escalating problem with complex impacts on both mother and fetus, while the standard Matrix Program is lengthy and difficult for pregnant women to access. This research and development (R&D) study aimed to develop a specialized treatment model for this vulnerable group in Wang Saphung District, Loei Province. This 3-phase R&D pilot study enrolled 30 pregnant women with methamphetamine-positive urine screening (census sampling of the target population during the study period; no control group). The model comprised screening, a 10-week CBT program, and continuous follow-up. Instruments showed a scale-level content validity index (S-CVI) of 0.85 and Cronbach’s alpha of 0.78. Data were analyzed using descriptive statistics, paired-samples t-test (with Cohen’s d), Chi-square goodness-of-fit, and Fisher’s Exact Test. Post-treatment, mean relapse-prevention attitude rose from M = 3.02 to M = 3.18 (t = 2.22, df = 29, p = .02, Cohen’s d = 0.45). During the 10-week program, 86.67% improved (26.67% abstinent, 60.00% reduced use), with no participant increasing their consumption, significantly exceeding the 70% target (χ² = 4.81, p = .028). At 3-month follow-up, 60.00% tested negative, and in-treatment behavior was significantly associated with non-relapse (Fisher’s Exact Test, p = .014). Overall satisfaction was high (M = 3.96). This pilot study indicates the CBT-based model is feasible and shows promising preliminary effects on attitudes and substance-use behavior. Scale-up requires testing in larger, multi-site samples.